Overcoming the Fear of Water at the Initial Stage of Learning to Swim - Olga Obrazhey (Lesya Ukrainka Volyn National University, 2017)
The article deals with the fear of children of primary school age to open water, which appears at the initial stage of teaching swimming and is a serious obstacle to mastering the skills of swimming. Analysis of the scientific researches indicate a lack of reasonable methods of overcoming fears associated with the water during swimming training and scientific methodological developments in the prevention and overcoming fears associated with water, which leads to certain problems and violations of logical consistency in teaching swimming. The following empirical methods as questionnaires, interviews, pedagogical observations are used. The article presents the results of a study of this problem, especially: the results of the survey of primary school children who arrived at the base of the summer camp «Lastochka» in Skadovsk of Kherson region in 2016 during the month of June as well as conversations and observations with them that took place in real conditions of training swimming. This study provided the opportunity to determine the origin of fear causes of primary school age children, to reveal the reasons and statistics of accidents at open water, to identify factors fear of open water of primary school age children. The article indicates signs of the most important physical symptoms associated with the fear of open water. Methodical recommendations developed to overcome fears at the initial stage of swimming lessons in open water based on the principles of psychological impact on the minds of everyone as well as the use of innovative techniques while swimming. Methodical recommendations focus on the preparation and organization of lessons with children of primary school age, with the problem of fear of open water. They aim to overcome fear and to achieve the main goals of the swimming lessons in the summer camp to teach swimming every child.